Motivación hacia la química - Morán, J. A. de; Bullaude, M. R. G. de; Zamora, M. M. K. de (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1995)
The attitude towards a discipline is decisively important for learning, especially for difficult subjects, such as Chemistry. In this paper we have intented to evaluate, into two groups of universitary students, the attitude towards Chemistry, the determinant factors, and the relationship between the attitude and the rank of knowledge of basic chemistry. Taking the results as a basis we propose methodologies to improve the development of favourable attitude towards Chemistry.